Religious Moderation Education from the Perspective of Educational Philosophy at Roudlatul Qur'an Islamic Boarding School, Metro, Lampung - M. Sayyidul Abrori; Alfin Auliya (CV. Creative Tugu Pena, 2025)
This study aims to examine religious moderation education from the perspective of educational philosophy at Roudlatul Qur'an Islamic Boarding School in Metro, Lampung. The background of this research is the increasing prevalence of religious radicalism and socio-religious conflicts in Indonesia, as well as the suboptimal implementation of religious moderation in Islamic boarding schools. This study employs an interpretative qualitative approach with a field research design. The research subjects include the boarding school leader, teachers, and students. Data were collected through participant observation, in-depth interviews, and documentation. Data validity was ensured through triangulation of sources, techniques, and time. Data analysis followed the Miles and Huberman model: data condensation, data display, and verification. The findings indicate that religious moderation education in this Islamic boarding school holds high urgency as a response to the complexity of contemporary religious life. Its implementation encompasses planning, execution, and evaluation, centered on the selection of moderate educators, wasathiyyah-based materials, and open learning methods. The philosophical construction integrates three pillars: values (derived from the Qur'an), processes (progressive), and objectives (pragmatic), while remaining grounded in Pancasila and maqasid al-shariah. This model is conceptualized as progressive, pragmatic, and religiously moderate education